Rendahnya Pengetahuan Gizi Ibu dan Defisiensi Asupan Energi Balita sebagai Faktor Risiko Stunting di Wilayah Pertanian: Low Maternal Nutrition Knowledge and Insufficient Energy Intake in Toddlers as Risk Factors for Stunting in Agricultural Areas - Zhafira, Shabrina Nuril; Pangestuti, Dina Rahayuning; Kartini, Apoina (Amerta Nutrition, 2024)
Background: Stunting is a significant nutritional problem in Indonesia, with higher incidence rates compared to other nutritional problems. Its influencing factors include toddler’s nutritional intake, parenting practices, environmental health, access to health services, mother’s education, and family food security. Objectives: This study sought to identify the most significant factors that contribute to the incidence of stunting in Sumowono District. Methods: This quantitative case-control study compared mothers of stunted toddlers (ages 12–59 months) against those of normally developing toddlers. Participants were selected through purposive sampling. The risk factors for stunting examined in this study included mother’s knowledge, family food security, toddler’s nutritional intake, mother’s age, father’s occupation, family income, Direct Cash Assistance (BLT) recipient status, parenting practices, access to health services, and environmental health. Data were collected using questionnaire surveys, observations, and 24-hour recalls. Data analysis used bivariate (chi-square) and multivariate (logistic regression) methods. Results: Most mothers of stunted toddlers had poor knowledge (81.1%) and lived in food-insecure families (86.5%). Bivariate tests showed associations between stunting and factors such as father’s occupation (p-value=0.019), family income (p-value=0.001), mother’s knowledge (p-value=0.001), family food security (p-value=0.001), energy intake (p-value=0.001), protein intake (p-value=0.001), vitamin A intake (p-value=0.036), vitamin D intake (p-value=0.027), zinc intake (p-value=0.036), parenting practices (p-value=0.011), and environmental health (p-value=0.001). The main factors found to influence stunting were mother’s knowledge (OR=19.144; CI: 1.919–190.953; p-value=0.012) and toddler’s energy intake (OR=227.996; CI: 16.899–3,076.100; p-value=0.001). Conclusions: The incidence of stunting in Sumowono District was significantly influenced by mother’s knowledge and toddler’s energy intake.